2002
DOI: 10.1007/s00122-002-0891-7
|View full text |Cite
|
Sign up to set email alerts
|

Genetic mapping of a dominant gene conferring resistance to cassava mosaic disease

Abstract: Cassava mosaic disease (CMD) is the most-important disease of cassava ( Manihot esculenta) in Africa, and is a potential threat to Latin American (LA) cassava production. Although this viral disease is still unknown in LA, its vector - the whitefly - has recently been found. The disease is best controlled through host-plant resistance, which was first found in third backcross derivatives of an interspecific cross between cassava and Manihot glaziovii, and is thought to be polygenic. Recently, high levels of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
180
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 183 publications
(205 citation statements)
references
References 17 publications
11
180
0
Order By: Relevance
“…The SSR markers found to be associated with the CMD resistance viz. SSRY28 from previous studies (Akano et al, 2002;Moreno et al, 2004;Lokko et al, 2005) and NS158 and SSRY106 from the present study are on the same linkage group covering a distance of 20.9 cM. Lokko et al (2004) identified seven different SSR markers associated with resistance to CMD in population derived from TMS30572 and TME117 and established the contribution of both the parents towards the resistance to CMD.…”
Section: Simple Sequence Repeat (Ssr) Analysissupporting
confidence: 71%
See 4 more Smart Citations
“…The SSR markers found to be associated with the CMD resistance viz. SSRY28 from previous studies (Akano et al, 2002;Moreno et al, 2004;Lokko et al, 2005) and NS158 and SSRY106 from the present study are on the same linkage group covering a distance of 20.9 cM. Lokko et al (2004) identified seven different SSR markers associated with resistance to CMD in population derived from TMS30572 and TME117 and established the contribution of both the parents towards the resistance to CMD.…”
Section: Simple Sequence Repeat (Ssr) Analysissupporting
confidence: 71%
“…However, Lokko et al (2005) identified two more DNA markers SSRY106 and E-ACC/M-CTC (an AFLP marker) having strong association with resistance to CMD. By considering the results of the present study and the studies of Akano et al (2002) and Lokko et al (2005), it is very clear that the genomic regions around the marker viz. SSRY28 harbours one of the major gene conferring resistance to CMD irrespective of resistance sources.…”
Section: Simple Sequence Repeat (Ssr) Analysissupporting
confidence: 58%
See 3 more Smart Citations